Na crise ucraniana: a península de Qirin… - Almeida, E. C. (Novo Jornal, 2014)
«Previous point, the Qirin peninsula is nothing more than the Tatar name of the region (the Scythian-Tauri), which was translated by the first modern conquerors, the Greeks (Dorians and Ionians), as Krimaia, that is, the Crimean peninsula . The peninsula was successively occupied by Cimmerians (Assyrians), Scythian-Sarmatians (ancient Persian people), Dorians and Ionians (Greeks), Goths and Huns (Germanic), Russians, Byzantine Turks and Mongols, Genoese and Ottoman Turks, these until 1777, definitively becoming occupied by the Russians in 1783. (...)»